Anaphylaxis as a Manifestation of Horse Allergy - Radoslaw Gawlik, MD; Tomas Pitsch; Lawrence DuBuske, MD (World Allergy Organization Journal, 2009)
Allergic disease induced by animal exposure is a common phenomenon worldwide. Whereas cat and dog dander exposure are well recognized as causative of allergic rhinitis, allergic asthma, and contact urticaria, horse allergy can present with anaphylaxis. Horse allergy is induced by exposure to the major horse allergens Equ 1 through 5. The severity of the symptoms may be related to the level of exposure. Greatest risk of anaphylaxis occurs in those sensitized patients who have large amounts of animal allergen exposure, such as when in a barn, or when an animal bite occurs exposing sensitized persons to large quantities of the animal allergen that resides in the saliva. Horse allergy may be successfully treated with allergen specific immunotherapy. Keywords: anaphylaxis, allergy, horse